I. Ligand-accelerated catalysis in palladium(II)-mediated carbon–hydrogen bond functionalisation, II. Hydrogen bonding effects on the reactivity of fluoride anion - Engle, K (2013)
Part I: "Ligand-Accelerated Catalysis in Palladium(II)-Mediated C–H Funtionalisation." A lingering problem in the area of Pd(II)-catalysed C–H functionalisation is the dearth of suitable ligands capable of lowering the activation energy for C–H cleavage. In our studies of aerobic Pd(II)-catalysed C–H olefination of phenylacetic acids, we discovered dramatic rate increases when mono-N-protected amino acids were used as ligands. In light of these findings, systematic ligand tuning was undertaken, resulting in major improvements in substrate scope, reaction rate, and catalyst turnover. A variant of this improved protocol was efficient in diolefination, offering a platform for sequential and iterative C–H functionalisation. We further demonstrated that amino acids ligands could enable efficient C–H functionalisation with other categorically distinct C–H functionalisation reactions, including C–H/R–BXn cross-coupling Part II: "Hydrogen Bonding Effects on the Reactivity of Fluoride Anion." Fluorine-containing compounds are becoming increasingly common as medicines, agrochemicals, and materials. As such, methods for C–F bond formation using nucleophilic (F–) and electrophilic (F+) sources of fluorine have witnessed a resurgence of interest in the past decade. In the field of nucleophilic fluorination with F–, a major challenge is tuning the reactivity profile of fluoride for specific applications. To this end, we studied the effect of intermolecular hydrogen bonding on the reactivity profile of fluoride anion with the goal of developing superior fluoride reagents for synthetic applications. To obtain a comprehensive mechanistic understanding, we combined kinetic, computational, and structural techniques, which revealed the importance of weak hydrogen-bond donors, which are capable of dissociating from fluoride in solution. This mechanistic work led to the development of a new class of shelf-stable, crystalline fluoride reagents for organic synthesis.